Humoral immunity in kidney transplantation what clinicians need to know - Remuzzi, Giuseppe 1949-; Chiaramonte, Stefano; Perico, Norberto; Ronco, Claudio 1951- (Contributions to nephrology, 2009)
As recent advances in immunosuppression and apheresis techniques have opened new avenues for the management of humoral immunity, interest in ABO-incompatible kidney transplantation has been renewed. Moreover, new screening techniques – such as the single antigen bead assay – allow for the detection and definition of very low levels of alloantibody, which has had a positive impact on the treatment possibilities in highly sensitized adult patients with end-stage renal disease. But despite these advances, a theoretical rationale is still missing for both the decision to transplant a sensitized patient and the classification of the transplant as low, medium or high risk. There is also no uniform approach with regard to pre-transplant desensitization protocols, and it is unclear whether particular post-transplant immunosuppression will be required and what would be the best combination treatment. Last but not least, the frequency and actual clinical impact of alloantibodies developed after transplantation on short- and long-term graft survival need to be ascertained.Aimed especially at the clinician, this publication presents recent insights in the characterization and pathogenetic role of humoral immunity in chronic allograft injury and investigates the perspectives for novel immunosuppressive therapies to control antibody production after transplantation